PENGARUH ORGANIZATIONAL CITIZEN BEHAVIOR DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN (Studi Kasus PT Sejahtera Utama Bersama Jombang) - Deni Widyo Prasetyo (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
The purpose of this study was to determine whether there is an influence between Organizational Citizenship Behavior and organizational communication to Employee Performance either partially or simultaneously. This research was conducted at PT. Sejahtera Utama Bersama Jombang. This type of research is explanatory. Data collection method used is survey method through the distribution of questionnaires to respondents. Population in this research is employees of PT. Sejahtera Utama Bersama. This research uses probability sapmling technique, with total sample 84 respondents. The test instrument used to test the hypothesis using multiple linear regression analysis. Hypothesis test proves that Organizational Citizenship Behavior (OCB) and Organizational Communication are proved to have a direct and significant influence on employee performance variable either simultaneously or partially. This research then give suggestion to PT. Sejahtera Utama Bersama Jombang to continue to maintain and improve the quality of Organizational Citizenship Behavior employees and organizational communication from the company so as to improve employee performance and able to create superior human resources and also potential that will become competitive advantage for the company Keyword :Organizational Citizenship Behavio, Organizational Communication and Employee Performance